THE EFFECT OF PRODUCT QUALITY AND DELIVERY SERVICE ON ONLINE-CUSTOMER SATISFACTION IN ZALORA INDONESIA - Handoko, Laras Putri (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2016)
The number of online transaction in Indonesia has increased in recent years with fashion products currently dominate the e-commerce market as the most frequently purchased products. The aims of this study are to analyze the effects of product quality and delivery service on online-customer satisfaction withdrawing taking online fashion retailer Zalora Indonesia as its research object. This research is causal type of research which uses primary data obtained through questionnaires and uses Multiple Regression Analysis. The population observed is people in Manado who have purchased Zalora Indonesia products online with 100 respondents as the sample size. The result of this study shows that product quality and delivery service have significant effects on online-customer satisfaction. To increase customer satisfaction, the recommendations for online shop owners are to maintain product quality, variety and availability in order to meet customer expectation as well as consistently offer reliable and safe delivery service at promised delivery schedule which encourage repeat purchases. Keywords: customer satisfaction, online shopping, product quality, delivery service